The effect of clothing on decomposition and scavenging in two forensically significant habitats in Cape Town, South Africa - Adams, Kara Sierra (Department of Human Biology, 2024)
In South Africa, identifying unknown human remains presents an ongoing challenge given the high murder rate in the country. A crucial aspect of the forensic death investigation involves estimating the postmortem interval, which is influenced by biogeographic factors specific to the region. To ensure the collection of forensically relevant data, the experimental design incorporated single, clothed individuals, as they constitute the majority of unidentified human remains in the Western Cape province. The effect of clothing on scavenging and decomposition were examined in two forensically significant habitats in Cape Town, South Africa. To explore the impact of clothing on scavenging and decomposition, research was conducted in two open habitats, one periurban habitat and one suburban habitat. Six clothed and uncaged porcine carcasses weighing 60kg each were deployed between July 2021 and January 2023 (FHS SEC REF 018_023 & 022_001). Data were collected on carcass mass loss over time, vertebrate scavenger activity, prevailing weather, and carcass tissue desiccation. A comparative sample of 16 unclothed carcasses deployed between 2014 and 2016 was analysed to assess the impact of clothing and biomass load on the decomposition rate. Overall, winter-season clothing delayed decomposition, but summer-season clothing accelerated the process. Carcass weight loss was directly affected by the scavenging of the Cape grey mongoose (Galerella pulverulenta), which accelerated the decomposition rate. Additionally, single carcasses within the same habitat decomposed quicker than the multi-carcass deployments. Natural precocious mummification is a unique phenomenon documented in the Western Cape province, and a novel component of this research was that it formed the first quantitative assessment of desiccation leading to precocious mummification. Printed computing boards inserted into the carcass tissue recorded full-thickness tissue moisture content from three sites on each carcass in 15-minute intervals. The data were analysed through generalised additive modelling with environmental temperature, humidity, solar radiation, and precipitation as covariates. Desiccation in summer appeared to follow an exponential decline, and temperature was the most influential environmental factor. These novel data demonstrate the potential of utilising accumulated degree days and moisture content to estimate the postmortem interval. The combined results advocate using single-clothed carcasses deployed across multiple seasonal trials in forensically significant locations to produce data that can be considered forensically realistic.